Czesław Miłosz in Postwar America - Kołodziejczyk, Ewa (De Gruyter, 2021)
Czesław Miłosz is at times called an American poet. This means one thing in Poland, and something else in the United States. To Polish readers, this description is mainly related to the moment of his departure from Europe to take up employment at the University of California in Berkeley, and his settlement for many years in California, where his new poems and essays were written. Miłosz is to them an American poet, in a biographical sense, from the time he started living at Grizzly Peak until his return to Krakow, and in a symbolic sense, for as long as he cooperated with the publishing market, participated in literary life, and was an ambassador of Polish literature across the ocean. He is an American poet to the extent that his work was influenced by the thought and work of those cultural circles.